Thermal decomposition of vanadyl Schiff-base compounds - David, H. L. [UNESP]; Lonashiro, M. [UNESP]; Benedetti, Assis Vicente [UNESP]; Zamian, J. R.; Dockal, E. R. (Elsevier, 1992)
The thermal stability and thermal decomposition of several Schiff bases coordinated to vanadyl, VO (Schiff base), were studied by thermogravimetry and conventional gas Chromatographic and X-ray analyses. The kinetics, the number of steps and, in particular, the final temperature of decomposition of these complexes depend on the equatorial ligand. © 1992.